A curiosity companion in a VR game for education - Tan, Mark Rong Hui (Nanyang Technological University, 2023)
Improving educational experiences is one of the major concerns of educational institutes around the world. Although gamification is one of the most popular methods of enhancing educational experiences, many different applications have been explored to further enhance the gamification of educational concepts. Virtual Reality (VR) has rapidly become a popular medium for educational games due to its ability to enhance learning through its immersive and interactive experiences. Additionally, developing educational games with a curious companion has been found to enhance students’ learning experiences and engagement. In this final year project, an educational game is created in the form of a VR Escape Room which also incorporates a Curiosity Companion, that covers the basic concepts of computer architecture in the computer science course. This project aims to create an educational game that can combine the application of VR and a curiosity companion, to create a highly immersive and engaging educational game for assisting computer science students to learn basic computer architecture concepts. This project will then be used to evaluate the effectiveness of combining VR and curiosity companion in enhancing the overall learning experience of students.